The diagnostic trajectory of developmental coordination disorder in the Netherlands: Experiences of mothers. (27th September 2021) - Lust, Jessica M.; Adams, Imke L. J.; Reinders‐Messelink, Heleen A.; Luijckx, Joli; Schoemaker, Marina M.; Steenbergen, Bert
Abstract: Background: Receiving a diagnosis can have a major impact on the child and its family. Parental satisfaction concerning the diagnostic trajectory is important with regard to acceptance and coping with their child's problems. Our aim was t o describe the diagnostic trajectory of developmental coordination disorder (DCD) in the Netherlands and identify factors that are related to parents' satisfaction. Method: Mothers of 60 children with a DCD diagnosis completed an online survey concerning their experiences during and after the diagnostic trajectory of obtaining this diagnosis. Results: Forty percent of the mothers rated the diagnostic trajectory towards a DCD diagnosis as stressful and 47% rated the knowledgeability of the first professional they consulted (mostly a general practitioner, paediatric physical therapist, or youth health care physician) as having no or just superficial knowledge about DCD. Around 60% of the mothers described a lack of knowledge and support at their child's school after receiving the diagnosis. Notwithstanding this, the majority of the participating mothers was (very) satisfied with the diagnostic trajectory. Higher appreciation of both the manner of the diagnosing professional and the post‐diagnostic support provided were predictive of higher satisfaction. Conclusions: Our results underline the importance of improving the knowledgeability in primary schools and primary health care professionals with regard to DCD.